1823 S.C. Acts 63 - (:unkn) unknown (My University, 1823)
Ch. 20, § 13: Prohibits any "free negro, or other free person of colour" from carrying any firearms or other military weapons without a written ticket from his or their guardian. Violators punished under pain of forfeiture.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES